UPAYA PEMERINTAH INDONESIA DAN AUSTRALIA DALAM PENYELESAIAN MASALAH PEMANFAATAN SUMBER DAYA LAUT DI PULAU PASIR DI TINJAU DARI HUKUM LAUT INTERNASIONAL - Kristoforus Emanuel Kake; Hendrik Saputra Doko; Theresia Yovita Putri Lengari (INTELIGENSIA MEDIA, 2024)
Disputes or conflicts whether private or public will lead to disagreement or understanding of the parties or other legal subjects. In international relations between countries harmony is needed in various activities, and this will not be achieved if the parties do not have good faith in resolving their disputes. Dispute resolution is therefore an important and decisive stage. When disputes occur between countries, international law plays an important role in this case sand island disputes using international law of the sea or UNCLOS. It provides guidelines, rules, and ways or methods of how a dispute can be resolved by the parties amicably. Dispute resolution efforts have become a concern for the international community, especially when facing disputes of a business nature that exceed the boundaries of a country's sovereign territory. Peaceful dispute resolution is a method that has been recognized and practiced for a long time until today. A State although subject to the obligation of peaceful settlement of disputes, it retains the authority to determine the manner or method of resolving its disputes. Its obligations remain subject to the agreement of the country concerned. From the results of the discussion, the author saw that there were several talks and meetings to solve the problem of Sand Island. Such as MOU BOX 1974 and Agreement On March 14, 1997 in Perth. agreement on the delimitation of the Exclusive Economic Zone (EEZ) and certain maritime boundaries and does not reduce the traditional rights of fishermen of Rote Island, East Nusa Tenggara. The proposed treaty would overcome maritime boundaries between Indonesia and Australia.